Strategi Branding Air Minum Dalam Kemasan Q-Jami' Produksi CV Masjid Agung Jami Malang - Utami, Ima Hidayati; Illahi, Azizun Kurnia (Akutansi Bisnis & Manajemen ( ABM ), 2016)
This study aims to describe the branding strategy emploied by packaged drinking water Q-Jami producer to make its brand widely known by the public and able to compete with similar products on the market. Employing a qualitative descriptive approach, the data is collected from primary and secondary data sources. The primary data was collected through interviews with 4 informants who were selected purposively and observations conducted on the site research, while the secondary data is taken from references, journals, and related documents. The informants consists of: the director of CV Masjid Agung Jami', the head of maintenance, and two employees. The findings reveal that: Firstly, before the brand name was released to the public, producer used four phases of strategic branding, namely: selecting unique brand name, selecting unique product feature, building brand personality characteristic, and creating distinctive visual identity. Secondly, producer run 6 steps of branding process to make the product widely known and competitive in the market, they are : designing appropriate logo, designing a good logo, using the word of mouth as a marketing tool, creating a messages that encourages cosumers to spread them, rewarding loyal distributors, and consistent with logo and design. Thirdly, brand name and brand personality built based on the issue of healthy as well as consuers religious norms values have fulfilled consumers particular emotional needs made them believe and loyal to the product rapidly.